2022
DOI: 10.3390/nu14112225
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Eating Enhances Intrinsic Capacity, Thus Promoting Functional Ability of Retirement Home Residents in Northern Taiwan

Abstract: Healthy aging is defined as the process of developing and maintaining functional ability in older age with intrinsic capacity, the composite of all the physical and mental capacities of an individual, being the core. This study was conducted to explore the intervention effects of improved dietary quality on intrinsic capacity. A prospective single-group interventional quasi-experimental study with 59 functional independent older adults from retirement homes were recruited. Texture-modified plant-based dietary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 49 publications
0
0
0
Order By: Relevance
“…Many previous studies have reported the association between IC and functional ability [4,[6][7][8][9][10]. Some studies have even proposed the mediating role that exists between IC and both basic activities of daily living (BADL) and instrumental activities of daily living (IADL) [4,8,9]. Recent evidence has also revealed the longitudinal relationship between IC and physical fitness or frailty [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies have reported the association between IC and functional ability [4,[6][7][8][9][10]. Some studies have even proposed the mediating role that exists between IC and both basic activities of daily living (BADL) and instrumental activities of daily living (IADL) [4,8,9]. Recent evidence has also revealed the longitudinal relationship between IC and physical fitness or frailty [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%